Application of Biotechnology in Specific Spoilage Organisms of Aquatic Products - Dong, Huina; Gai, Yuanming; Fu, Shaoping; Zhang, Dawei (Frontiers in Bioengineering and Biotechnology, 2022)
Aquatic products are delicious and have high nutritive value, however, they are highly perishable during storage due to the growth and metabolism of microorganisms. The spoilage process of aquatic products was demonstrated to be highly related to the composition of microorganisms, in which the specific spoilage organisms (SSOs) are the main factors. In this article, the spoilage indicators of SSOs were systematically described, which could make a comprehensive evaluation of the quality of aquatic products. Quorum sensing (QS) regulates the growth, metabolism and characteristics of SSOs, the common signaling molecules and the QS system in the major SSOs of aquatic products were discussed. Moreover, we compared various technologies for the analysis of SSOs in aquatic products. Besides, quality control techniques based on microbiota regulating of aquatic products, including physical, chemical and biological preservation strategies, were also compared. In conclusion, novel preservation technologies and hurdle techniques are expected to achieve comprehensive inhibition of SSOs.